2019
DOI: 10.22159/ajpcr.2019.v12i5.33005
|View full text |Cite
|
Sign up to set email alerts
|

Development, Evaluation and Targeting of Stavudine Loaded Serum Albumin Polymer Based Nanocarriers to Hiv Reservoirs

Abstract: Objective: Stavudine is an antiretroviral drug that is part of the nucleoside reverse transcriptase inhibitor (NRTIs) family, which is used to delay the progression of HIV infection. The present investigation involves the development and evaluates stavudine loaded nanocarriers using natural polymer bovine serum albumin (BSA). Methods: The desolvation technique was used to prepare nanoparticles and coated with 1% v/v polysorbate 80 to improve the targeting of drugs to the organs (HIV reservoirs). Biodistr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“… 68 Based on the literature study ( Table 2 ), six studies discussed optimization by varying the ratio of drug: BSA. According to Abd Ellah et al 69 Jenita, Wilson, and Chocalingam, 70 Spada et al 71 Jenita, 72 and Syed and Sailaja 73 the particle size and polydispersity index value increase with the amount of BSA used. This is in accordance with previous studies also stating that the higher the concentration of BSA, the larger the particle size and the greater the polydispersity index.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“… 68 Based on the literature study ( Table 2 ), six studies discussed optimization by varying the ratio of drug: BSA. According to Abd Ellah et al 69 Jenita, Wilson, and Chocalingam, 70 Spada et al 71 Jenita, 72 and Syed and Sailaja 73 the particle size and polydispersity index value increase with the amount of BSA used. This is in accordance with previous studies also stating that the higher the concentration of BSA, the larger the particle size and the greater the polydispersity index.…”
Section: Methodsmentioning
confidence: 99%
“…This relationship can be explained through the classical nucleation theory. 65 On the other hand, several studies have reported that increasing BSA concentrations only had a slight influence on the size of BSA nanoparticles. 55 Radwan SES et al stated that an increase in BSA concentration from 2.5% to 10% resulted in a decrease in particle size from 260 nm to 100.5 nm.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations